E OF ACTIVE METHODOLOGY IN NURSING GRADUATION COURSES (CIPEEX, 2022)
INTRODUCTION: THE ACTIVE METHODOLOGIES OF TEACHING AND LEARNING, PARTICULARLY WITH A PROBLEMATIZING APPROACH, HAVE BEEN USED IN THE TRAINING AND QUALIFICATION OF HEALTH PROFESSIONALS, AS A STRATEGY FOCUSED ON THE INTEGRATION OF KNOWLEDGE AND THE PROMOTION OF A CRITICAL AND REFLEXIVE ATTITUDE ABOUT THE PRACTICE. IN NURSING UNDERGRADUATE EDUCATION, IT IS AN IMPORTANT TOOL TO STIMULATE THE CRITICAL-REFLECTIVE REASONING OF THE GRADUATE AND TO MEET THE PROFESSIONAL PROFILE PROPOSED BY RESOLUTION CNE / CES NO. 3 OF NOVEMBER 7, 2001, WHICH IS ESTABLISHED IN ARTICLE 3 OF THE GUIDELINES NATIONAL CURRICULA OF THE UNDERGRADUATE NURSING COURSE (DCNS). OBJECTIVE: TO DESCRIBE THE APPLICABILITY OF THE ACTIVE METHODOLOGY IN UNDERGRADUATE NURSING COURSES IN ORDER TO OBTAIN THE SKILLS AND COMPETENCES REQUIRED BY THE NURSING PROFESSIONAL IN ACCORDANCE WITH THE NATIONAL CURRICULAR GUIDELINES (DCNS). METHODOLOGY: THIS IS AN INTEGRATIVE REVIEW OF THE LITERATURE COMPOSED OF ARTICLES PUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL) AND AVAILABLE IN FULL TEXT IN THE DATABASES: LILACS, MEDLINE AND BDENF, IN THE PERIOD BETWEEN 2010-2016. AMONG THE SEARCH CRITERIA, ARTICLES WERE ADOPTED IN FULL IN PORTUGUESE; AMONG THE EXCLUSION CRITERIA WERE ADOPTED: ARTICLES IN OTHER LANGUAGES €‹€‹THAT DID NOT CONTEMPLATE THE PROPOSED PERIOD AND WHICH DID NOT RESPOND TO THE OBJECT OF STUDY. TO ANALYZE THE DATA, THE RECOMMENDATIONS OF MENDES ET AL. (2008). RESULTS: THE DATA WERE ORGANIZED INTO TABLES, SYNOPTIC TABLES, FIGURES AND LATER CATEGORIZED. FIFTEEN ARTICLES WERE INCLUDED IN THE PRESENT STUDY. FROM THE CRITICAL AND DETAILED ANALYSIS OF THE ARTICLES SUBMERGED THE FOLLOWING CATEGORIES: NEW DISCOVERIES AND CHALLENGES OF THE LEARNING TEACHING PROCESS IN UNDERGRADUATE NURSING COURSES; AND TEACHING-LEARNING STRATEGIES IN UNDERGRADUATE NURSING COURSES. CONCLUSION: THE STUDY EVIDENCED DIFFICULTIES IN RELATION TO THE ACTIVE TEACHING / LEARNING METHODS IN THE TRAINING OF NURSES, EDUCATIONAL INSTITUTIONS AND THE TEACHERS THEMSELVES HAVE TO THINK, AND RETHINK THE CONSTRUCTION OF NEW VIABILITY OF ACTIONS THAT MODIFY THE WAY OF ACTING FOR THE SCOPE SUCCESS IN THE TEACHING-LEARNING PROCESS.
Keywords: Methodology. Active Methodology. Nursing Education. Nursing Education